Enjeux du jeu de mots. Perspectives linguistiques et littéraires - Winter-Froemel, Esme; Zirker, Angelika (De Gruyter, 2015)
In conjunction with the first volume of the series, this collection of essays analyzes techniques and basic traditions of wordplay in various communicative situations and offers new perspectives on the dynamics of wordplay as an interface phenomenon.
French
Keywords: Wordplay; Linguistic Innovation; Metalinguistic Reflection